The Purpose and Age of Underwater Walls in the Bay of Elaia of Western Turkey: A Multidisciplinary Approach. Issue 2 (March 2014) - Seeliger, Martin; Brill, Dominik; Feuser, Stefan; Bartz, Melanie; Erkul, Ercan; Kelterbaum, Daniel; Vött, Andreas; Klein, Christina; Pirson, Felix; Brückner, Helmut
<x xml:space="preserve">Abstract</x> Pergamum (modern: Bergama) was operating an important harbour used by military forces and merchants at the city of Elaia during Hellenistic and Roman Imperial times. Harbour‐related facilities such as warehouses, breakwaters and wharfs document the importance of this harbour site not only for the Pergamenians. This paper focuses on the purpose and age of six submerged wall structures situated approximately 1 km south of the ancient closed harbour basin of Elaia. Geoelectric cross‐sections and semi‐aquatic coring near these walls failed to detect any solid basement under the walls which excludes their possible use as breakwaters or wharfs. Instead, the walls were most likely delineating and separating evaporation ponds of salt works, which compares well with similar structures from other periods and places around the Mediterranean. Combined OSL and 14C‐dating determined the construction age of the installation between the 4th and 6th centuries A.D. Subsequent (re‐)uses are likely and are in agreement with findings from archaeological surveys.